Emerging Rickettsioses of the Thai-Myanmar Border - Philippe Parola (Emerging Infectious Diseases, 2003)
To investigate the presence of rickettsioses in rural residents of the central Thai-Myanmar border, we tested the blood of 46 patients with fever. Four patients had murine typhus, three patients had scrub typhus, and eight patients had spotted fever group rickettsioses, including the first case of Rickettsia felis infection reported in Asia.